Radicalism and Salafism in Indonesia: Development and Movement of Transnational Ideology - Setiawati, Rini; Hidayat, Rahmat; Mukri, Moh. (Analisis: Jurnal Studi Keislaman, 2024)
Radicalism and Salafism in Indonesia are important issues that are closely related to the development of transnational ideology. The background to the emergence of this movement cannot be separated from the influence of globalization and technological advances, which facilitate the spread of extreme ideologies such as Wahhabism and Salafism among some Muslims. The Salafi movement, which emphasizes the purification of Islamic teachings by interpreting religious texts literally without considering the social, cultural, and historical context, has the potential to damage the pluralism and tolerance that have become the hallmarks of Indonesia. The main problem faced is the increasing radicalization that can trigger social conflict and threaten national unity. This study uses a qualitative and phenomenological approach with descriptive-analytical methods, as well as data analysis that include data reduction, data presentation, and inductive drawing of conclusions. The results of the study show that radicalism and Salafism in Indonesia developed through a transnational ideology that prioritizes a textual understanding of Islam without considering the social and cultural context. This movement risks exacerbating social tensions and threatening Indonesia's diversity. Therefore, Indonesia needs to strengthen its understanding of moderate Islam and the values of pluralism to face this challenge and maintain social harmony.